Very low blood flow carbon dioxide removal system is not effective in a chronic obstructive pulmonary disease exacerbation setting. Issue 5 (21st December 2020) - Giraud, Raphaël; Banfi, Carlo; Assouline, Benjamin; De Charrière, Amandine; Bendjelid, Karim
Abstract: Extracorporeal carbon dioxide removal (ECCO2 R) is a low blood flow veno‐venous extracorporeal membrane oxygenation technique that provides artificial blood CO2 removal. Recently, a new ECCO2 R system (PrismaLung), providing very low blood flow has been commercialized. The aim of this study is to report its use in severe chronic obstructive pulmonary disease (COPD) patients needing an ECCO2 R therapy. Six severe COPD patients with acute exacerbation leading to refractory hypercapnic respiratory acidosis were treated with ECCO2 R therapy. Two different systems were used: a PrismaLung system and a conventional ECCO2 R device. The maximum blood flow provided by PrismaLung was significantly lower than that with the conventional ECCO2 R system. In three patients initially treated with PrismaLung, there were no improvements in pH, PaCO2, or RR. Thus, the therapy was switched to a conventional ECCO2 R system in these three patients, and three others were treated from the outset by the conventional ECCO2 R system, providing significant improvement in pH, PaCO2, and RR. The present retrospective study describes the first use of PrismaLung in severe COPD patients with acute exacerbation. When compared with a higher blood flow ECCO2 R system, our results show that this novel, very low‐flow device is not able to remove sufficient CO2, normalize pH or decrease respiratory rate. Abstract : Very‐low flow ECCO2 R device using a 13Fr dialysis catheter(A) is not able to remove sufficient CO2, normalize pH or decrease respiratory rate compared with a higher blood flow ECCO2 R system using a 19Fr duallumencannula (B). ECCO2 R: Extracorporeal CO2 removal, SVC: Superior Vena Cava, RA: Right Atrium, TV: Tricuspid Valve, IVC: Inferior Vena Cava.